The Savings Trap and Economic Take-Off - Ghosh, Atish (IMF Working Papers; Working Paper ;, 1992)
We develop an overlapping generations model of a developing economy in which 'culture' and technology interact to determine savings, investment and growth. Investment is assumed to involve intermediation or other costs which may, in each period, result in either of two stable equilibria for the savings rate. At the 'good' equilibrium, savings and growth are higher than at the 'bad' equilibrium, whether the country attains the good or bad equilibrium in any period depends on each individual's belief about the savings behavior of other agents in the economy. The model implies that fiscal policy or public activities to facilitate private investment can influence saving. In particular, a sustained period of fiscal restraint can shift the economy onto a higher savings and growth path.